Validity and Reliability of the Adolescent Lifestyle Profile-Revised 2 (ALP-R2) Scale in Colombian Adolescents - Herrera Guerra, Eugenia del Pilar; Bautista Arellanos , Lili Rosa; Bonilla Ibáñez, Claudia (Investigación y Educación en Enfermería, 2024)
Objective. The study sought to determine the validity and reliability of the Adolescent Lifestyle Profile-Revised 2 (ALP-R2) scale, translated into Spanish, in Colombian adolescents. Methods. Psychometric study, which included the translation process (English to Spanish). The final version of the scale in Spanish was approved by Nola Pender; apparent and content validation was carried out through expert judgment (n = 6). With a sample of 1476 Colombian adolescents. Construct validity was determined through exploratory and confirmatory factor analysis. The internal consistency was calculated with Cronbach’s coefficient. Results. Favorable evidence was obtained of apparent validity, content validity, and construct validity with a model comprised of 44 items and 7 subscales (total accumulated variance 44.9%) with good absolute fit (χ2: 18434.3; df = 946; p < 0.0001; CMIN/DF = 4.326; SRMR = 0.0562; RMSEA = 0.047), incremental (CFI = 0.834; NFI = 0.795; NNFI = 0.822) and parsimony (PCFI = 0.777; PNFI = 0.741; AIC = 4116.848). Good internal consistency in the total scale (α = 0.91) and in the subscales (α between 0.609 and 0.809). Conclusion. The Spanish version of the ALP-R2 scale has adequate psychometric properties of validity and reliability, to measure the lifestyle profile of Colombian adolescents, coherent with the theoretical model of Health Promotion. Its use is recommended in populations similar to that of the study.